Distribution and Attachment of Bryozoans in the Intertidal Region of South Andaman Island - Naufal, Mohammed; Pathan, Anil; Jayaraj, Kaderambil Arjunan (Journal of Tropical Life Science, 2018)
Aiming to collate the distribution and the attachment preference of intertidal bryozoan of Andaman waters, a study was carried out in three intertidal sites (Burmanallah, Kodiyaghat, and Chidiytapu) of southeastern coasts of the Andaman Islands between June and August 2016. The present study is the first exclusive report on bryozoans from the Andaman Islands after a long research gap of nine decades. During our investigation, a total of twelve genera were identified from both calcareous and non-calcareous substratum. Out of the twelve genera, eight genera were new records from the island. The present study showed that the attachment affinity of the Bryozoans is more towards natural substratum particularly on the rocks. The Thalamoporella sp. reported the most abundant species with maximum average colony length of 3.5 cm from the rock substratum.